2008
DOI: 10.1074/jbc.m801195200
|View full text |Cite
|
Sign up to set email alerts
|

Logical Identification of an Allantoinase Analog (puuE) Recruited from Polysaccharide Deacetylases

Abstract: The hydrolytic cleavage of the hydantoin ring of allantoin, catalyzed by allantoinase, is required for the utilization of the nitrogen present in purine-derived compounds. The allantoinase gene (DAL1), however, is missing in many completely sequenced organisms able to use allantoin as a nitrogen source. Here we show that an alternative allantoinase gene (puuE) can be precisely identified by analyzing its logic relationship with three other genes of the pathway. The novel allantoinase is annotated in structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…1). This conjecture was confirmed by Ramazzina et al, who recently identified the HpxB homolog from Pseudomonas fluorescens DSM 50090 as an (S)-allantoin-specific allantoinase (76). They denote this enzyme PuuE.…”
Section: Nal Fmn Binding Domain (Consensus Sequences R-x-y-s-l and Gsupporting
confidence: 68%
See 2 more Smart Citations
“…1). This conjecture was confirmed by Ramazzina et al, who recently identified the HpxB homolog from Pseudomonas fluorescens DSM 50090 as an (S)-allantoin-specific allantoinase (76). They denote this enzyme PuuE.…”
Section: Nal Fmn Binding Domain (Consensus Sequences R-x-y-s-l and Gsupporting
confidence: 68%
“…employ HpxA allantoin racemase, related to hydantoin racemases (72,94), as well as the HpxB (PuuE) allantoinase, related to polysaccharide deacetylases and described recently by Ramazzina and coworkers (76). Our work in progress indicates further that other previously undescribed enzymes are involved in allantoate catabolism (Fig.…”
Section: Nal Fmn Binding Domain (Consensus Sequences R-x-y-s-l and Gmentioning
confidence: 57%
See 1 more Smart Citation
“…The protein encoded by hpxB displays allantoinase activity. The protein encoded by gene hpxB (KPN_ 01787) in K. pneumoniae displayed 89% identity with HpxB of K. oxytoca (28) and 58% identity with the metal-independent allantoinase encoded by puuE in Pseudomonas fluorescens (29). In K. oxytoca, the ortholog hpxB gene was proposed to encode allantoinase since hpxB insertion mutants failed to grow with allantoin as the sole nitrogen source but displayed normal growth with allantoate (28).…”
Section: Vol 193 2011 Allantoin and Guanine Metabolism In K Pneumomentioning
confidence: 99%
“…Instead, this protein displays high similarity to PuuE, a novel allantoinase of Pseudomonas fluorescens that is annotated in structure and sequence databases as polysaccharide deacetylase on the basis of its similarity to enzymes that remove Nlinked or O-linked acetyl groups from cell wall polysaccharides (29). As for HpxB, other enzymes of the purine catabolic pathway encoded in K. pneumoniae, such as xanthine oxidase (hpxDE) and uricase (hpxO), do not display similarity to other reported enzymes known to catalyze these reactions (10).…”
Section: Vol 193 2011 Allantoin and Guanine Metabolism In K Pneumomentioning
confidence: 99%